Hypoglycemic effect of Bromelia plumieri (E. Morren) L.B. Sm., leaves in STZ-NA-induced diabetic rats - Andrade-Cetto, Adolfo; Medina-Hernández, Anamarel E. (Frontiers in Pharmacology, 2013)
This study confirms the hypoglycemic effects of two extracts obtained from the Bromelia plumieri (BP) plant in streptozotocin-nicotinamide induced diabetic rats (STZ-NA). BP has been traditionally used in the municipality of Hidalgo, Mexico, to treat type 2 diabetes (T2D). Two different BP extracts were prepared and tested. The first extract was a water extract (WE), similar to that traditionally used to make tea, and the second extract was an ethanol:water extract (EWE). The extracts (WE at 35 and 350 mg/kg, and EWE at 30 and 300 mg/kg) were tested in STZ-NA induced diabetic rats to determine whether hypoglycemia occurred after administration of the extracts. Phytochemistry: Two different extracts were prepared, n-hexane and butanol, to determine the presence of alkaloids, terpenes and flavonoids. The extracts that were administered to the STZ-NA induced diabetic rats produced a significant hypoglycemic effect as compared with the control group, similar to that achieved with glibenclamide. We also determined that flavonoids were the main components of BP leaves. The results presented here support the hypothesis that extracts obtained from this plant have hypoglycemic effects, which are in agreement with the traditional uses of this plant.